Online Grocery Shopping Behavior among Consumers in Singapore - Vasudevan, Asokan; Ping, Tan Ping; Wider, Walton (International Journal of Management and Sustainability, 2022)
The globalization trend during the Covid-19 pandemic showed that there are more consumers willing to shop online than visit physical stores. The purpose of this study is to investigate the influence of convenience, service quality, and social factors on consumer online grocery shopping behavior in Singapore during the Covid-19 pandemic. Data were collected from 153 respondents in Singapore via a survey, which was distributed through an online platform. A cross sectional study was applied, and the research instruments used were adapted from several past studies. Research hypotheses were analyzed using partial least squares structural equation modeling (PLS-SEM). The results indicate that convenience (β = 0.360, t = 4.063, p < 0.01) and service quality (β = 0.416, t = 5.495, p < 0.01) significantly influence consumer online grocery shopping. However, social factors (β = 0.042, t = 0.490, p > 0.05) have no significant influence on consumer online grocery shopping. With the help of the Theory of Planned Behavior, the present study has provided support for previous studies as well as clarified the roles played by convenience, service quality, social factors in consumer online grocery shopping behavior in Singapore.